Research on the Mechanism of Preventing and Resolving Ideological Risks in Universities under the Background of Sino Foreign Cooperation - Liu, Yuting (Journal of Theory and Practice of Contemporary Education, 2023)
Universities bear the important responsibility and mission of educating people for the Party and the country, and are the forefront of ideological and political education and ideological work in universities. In the context of Sino foreign cooperative education, the ideological and political education and ideological work in universities are facing new challenges and risks. Therefore, universities with such backgrounds should effectively strengthen their awareness of preventing and resolving ideological risks, Strengthen the construction of risk prevention and resolution mechanisms in the ideological field to ensure campus harmony and stability.